SAT0339 NERVOUS SYSTEM INVOLVEMENT IN SYSTEMIC SCLEROSIS: A COHORT STUDY. (2nd June 2020) - Porel, T.; DE Almeida Chaves, S.; Adoue, D.; Astudillo, L.; Ribes, D.; Prévôt, G.; Gaches, F.; Michaud, M.; Alric, L.; Sailler, L.; Pugnet, G.
Abstract : Background: Nervous system involvement is considered to be rare in systemic sclerosis (SSc). Its prevalence is highly variable in SSc cohort studies and its prognosis is not well established. Objectives: To determine the frequency, clinical characteristics, associations, and outcomes of different types of peripheral nervous system (PNS) and central nervous system (CNS) disease in a cohort of systemic sclerosis patients. Methods: We have carried out a retrospective observational study by systematically analyzing the medical records of patients diagnosed with SSc in Toulouse University Hospital and Ducuing Hospital, south west France. We included patients who met the following inclusion criteria: being over 18 years of age on diagnosis, meeting the ACR /EULAR 2013 classification criteria, being diagnosed after 01/01/1966 and before 31/12/2018, at least 12 months of follow-up. Patients were followed until 31/12/2019. Nervous system involvement associated with SSc was included when there was involvement on or after diagnosis and after exclusion of all other causes. Only symptomatic clinical involvement was included. Ischemic or hemorrhagic strokes were excluded. We calculated the incidence of CNS and/or PNS disease during the follow-up period per 1, 000 person-years. Kaplan-Meier curves were plotted to determine the cumulative incidence of nervous system disease. We evaluated associated factors of CNS and/or PNS disease using multivariable Cox regression. Results: Of 447 SSc patients, 79.8% were female, 68 (15%) were diffuse cutaneous SSc, 342 (77%) were limited cutaneous SSc and 37 (8%) were sine scleroderma SSc. The mean ± SD age at diagnosis was 52.9 ± 14.3 years. During the study period, 82 (18%) patients experienced a PNS disease, 29 (6%) a CNS disease. The incidence was 28 per 1, 000 patient-years of any nervous system disease, with 22 per 1, 000 patient-years and 6 per 1, 000 patient-years of PNS disease and CNS disease, respectively. The most frequent were carpal tunnel syndrome (63%) and polyneuropathies (12%) for PNS disease, and headache (45%) and seizures (10%) for CNS disease. Three significant independent associated factors with PNS disease occurrence were identified using multivariable Cox regression: BMI>23.1kg/m 2 (HR = 1.06 [1.01-1.12]), joint involvement (HR = 2.7 [1.3-5.5]), and an alteration in the left ventricular ejection fraction (HR = 3.8 [1.4-10.3]). Four significant independent associated factors with CNS disease occurrence were identified: age > 54 years (HR = 2.5 [1.1-6.0]), positive anti-PmScl testing (HR = 6.4 [1.5-28.2]), Caucasian origin (HR = 0.2 [0.1-0.5]) and hemoglobin < 12g/dl (HR = 0.2 [0.04-0.8]). Nervous system disease occurrence did not appear to have a negative impact on the survival of SSc patients (log-rank p=0.56). Conclusion: This study shows that specific nervous system disease in SSc is not uncommon and does not appear to increase mortality, but it could have an impact on functional prognosis and needs to be monitored. Disclosure of Interest: None declared